Corporate social responsibility, channel coordination and profit division in a two-echelon supply chain. Issue 1 (2nd January 2016) - Panda, S.; Modak, N.M.; Pradhan, D.
Abstract : This paper deals with coordination and profit division in a manufacturer–retailer supply chain with corporate social responsibility (CSR). Considering the retailer to be socially responsible in one case, and the manufacturer to be so in another, the paper applies a quantity discount contract to resolve channel conflict. It is found that the retailer's perfect welfare maximizing motive is enough for channel coordination. When a channel member is not the perfect welfare maximizer, a quantity discount contract cuts out channel conflict. The wholesale price of a quantity discount contract is different from that of a traditional profit maximizing supply chain. It may be equal to the manufacturer's decentralized wholesale price in one case, and negative for CSR above a certain threshold in another. Also, the manufacturer's pure profit may be negative if it puts a heavy weight on CSR. Using the Nash bargaining product, the surplus profit is divided between the channel members. It is found that, for pure profit, a channel member always prefers the other members to be corporately socially responsible.